Bidding for successful academic enculturation: the story of a home-trained, home-based non-Anglophone scientist. Issue 1 (2nd January 2022) - Sun, Xiaoya; Cheung, Yin Ling
ABSTRACT: Academic enculturation, or the socialisation into a target academic community, is a crucial event in the trajectory development of aspiring scholars. It is a protracted process subject to the interplay of a constellation of factors. With the aim of uncovering potential contributors to positive enculturative outcomes, this paper reports on the case of Wang, a home-trained, home-based Chinese scientist who earned full professorship at the relatively young age of 36. An in-depth, semi-structured interview is conducted in which Wang gives retrospective accounts of significant experiences in his journey. A range of supplementary information, including representative publications, an up-to-date list of scholarly achievements, and his personal webpage at the official institutional website, is also collected to corroborate and add nuance to Wang's self-told story. Data are analysed using the method of inductive content analysis and discussed within the framework of situated learning theories. Varying extents of mutual engagement with/as the master and mutually facilitative dual engagement in target communities are found to characterise Wang's enculturative success. Implications are drawn on how similarly positioned novice researchers can be supported in their quest for enculturation during and beyond graduate studies.